A Design of Interactive Augmented Reality Mobile-Learning Application for iOS-Based Device: Phytochemical Screening Material - Ruth Elenora Kristanty; Nashrul Hakiem (Graduate School of Universitas Negeri Malang, 2022)
Abstract: Augmented Reality (AR) in the study of phytochemical screening is a technology that combines observation of experimental results in phytochemical screening as virtual objects with real environments. This study aimed to develop interactive learning media for phytochemical screening materials in the Phytochemistry Practicum at the Pharmaceutical and Food Analysis Department of Poltekkes Kemenkes Jakarta II. This interactive learning media application using AR technology was applied to iOS-based smartphones and designed for phytochemistry learning in the laboratory. The methods used in this study were descriptive exploratory for phytochemistry analysis and Multi-Media Development Life Cycled (MDLC) for AR development. 3D objects were resulting from phytochemical screening of Simplicia powder studied by using blender application, with Unity as a game engine and Vuforia as a library. The development of AR technology resulted in iOS-based mobile application named AR Fitokimia that visualized the phytochemical screening results. The application would help improve students' understanding and participation in distance learning. An interactive AR mobile learning application for iOS-based smartphones was designed for the entire class with an iFamily device in handling distance learning of phytochemical screening in the laboratory.Abstrak: Augmented Reality (AR) dalam kajian penapisan fitokimia merupakan teknologi yang menggabungkan pengamatan hasil eksperimen penapisan fitokimia sebagai objek virtual dengan lingkungan nyata. Tujuan penelitian ini adalah mengembangkan media pembelajaran interaktif untuk materi skrining fitokimia pada mata kuliah Praktikum Fitokimia di Jurusan Analisis Farmasi dan Makanan Poltekkes Kemenkes Jakarta II. akan diterapkan pada smartphone berbasis iOS dan dirancang untuk pembelajaran fitokimia di laboratorium. Metode yang digunakan dalam penelitian ini adalah deskriptif eksploratif untuk analisis fitokimia dan Multi-Media Development Life Cycled (MDLC) untuk pengembangan AR. Hasil skrining fitokimia beberapa serbuk simplisia dijadikan sebagai objek 3D menggunakan aplikasi Blender, dengan Unity sebagai game engine dan Vuforia sebagai library. Pengembangan teknologi AR menghasilkan aplikasi mobile berbasis iOS dengan nama AR Fitokimia yang memvisualisasikan hasil skrining fitokimia. Aplikasi ini akan membantu meningkatkan pemahaman dan partisipasi siswa dalam pembelajaran jarak jauh. Aplikasi pembelajaran mobile AR interaktif untuk smartphone berbasis iOS dapat dirancang untuk seluruh kelas dengan perangkat i-Family dalam mengatasi pembelajaran jarak jauh skrining fitokimia di laboratorium.